(untitled) (Revista Interdisciplinar Pensamento Científico, 2021)
The intense changes in the world economy created a scenario of great uncertainty for the financial market investor. Uncertainties cause risks, which can be understood as the probability of capital loss due to exposure to the market. The Brazilian investor, traditionally considering its conservative profile, faces major problems against risk, since traditional investments, with lower profitability and greater security, are no longer proving advantageous. Without proper risk analysis, this investor is very susceptible to corrosion of his capital. The present work of conclusion of course aims to expose the main concepts of risk analysis, considering the theoretical and practical nuances that involve this type of action, giving the possibility of robustness and strengthening of methodologies for the gathering of an information framework to assist in taking decisions, in order to avoid undesirable risks or minimize impacts on its assets.